2005
DOI: 10.1002/cncr.21433
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term disease‐free survival of patients with radically resected thymomas

Abstract: BACKGROUNDDespite radical surgical resection, thymomas often recur. The objective of the current retrospective study was to investigate the prognostic relevance of the expression of cell‐cycle proteins in these neoplasms to formulate a possible therapeutic surveillance strategy for the prevention of recurrence.METHODSThe authors retrospectively reviewed the main clinicopathologic factors, including the World Health Organization (WHO) classification, of patients with thymoma who had undergone radical surgical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…40 The prognostic role of p21 expression in radically-resected thymoma has been described by Mineo et al who found an association between low tumoral expression of p21 and reduced disease-free survival. 41 Although our data indicate a possible predictive role of p21 expression, given the small sample sizes, the significance of this finding will have to be further evaluated in larger samples. Detection and visualization of γ-H2AX, the phosphorylated form of the H2AX protein, provides a useful assessment of DNA damage.…”
Section: Discussionmentioning
confidence: 77%
“…40 The prognostic role of p21 expression in radically-resected thymoma has been described by Mineo et al who found an association between low tumoral expression of p21 and reduced disease-free survival. 41 Although our data indicate a possible predictive role of p21 expression, given the small sample sizes, the significance of this finding will have to be further evaluated in larger samples. Detection and visualization of γ-H2AX, the phosphorylated form of the H2AX protein, provides a useful assessment of DNA damage.…”
Section: Discussionmentioning
confidence: 77%
“…Compared with thymoma, it has more expression in thymic carcinoma, and it also has higher expression levels in invasive thymoma than in noninvasive thymoma. Other studies have shown that P53 is also associated with shorter disease-free survival and overall survival[16]. Overexpression of HER2 is rare in thymoma but relatively common in thymic carcinoma[15].…”
Section: Discussionmentioning
confidence: 99%
“…MG varlığı, ileri yaş, tümör çapı (≥8 cm), hücre siklus protein ekspresyonu gibi birçok faktör ek prognostik faktör (PF) olarak tanım-lanmıştır (27)(28)(29) .…”
Section: Discussionunclassified